THE ROLE OF ISLAMIC EDUCATION IN OVERCOMING BULLYING IN SMP NEGERI 4 LUBUK PAKAM: Peran Pendidikan Islam Dalam Mengatasi Bullying Di Smp Negeri 4 Lubuk Pakam - Maisarah, Maisarah; nisa, nurun (STAI Ma'had Aly Al-Hikam Malang, 2025)
Bullying among junior high school students is still a serious problem that negatively affects the psychological and social well-being of students. This study aims to analyze the role of Islamic education in preventing and overcoming bullying behavior at SMP Negeri 4 Lubuk Pakam. The approach used in this research is qualitative with descriptive method. Data were collected through in-depth interviews, participatory observation, and documentation studies involving Islamic Religious Education (PAI) teachers, students, and school policies related to bullying prevention. The results showed that the internalization of Islamic religious values contributes to shaping the character of students who are more tolerant, empathetic, and respectful of others. However, the approach used by schools in dealing with bullying is still reactive, focusing more on counseling and mediation after the incident rather than preventive strategies. Islamic education has provided a moral foundation for students, but its effectiveness is still affected by less interactive teaching methods. To increase the effectiveness of Islamic education in preventing bullying, innovations in learning methods are needed, such as group discussions, case simulations, and family involvement in building a positive social environment. The implication of this study shows that the integration of Islamic education with a more interactive and systematic approach can strengthen bullying prevention efforts in schools.